ChemInform Abstract: PhICl2‐Mediated Conversion of Enamines into α, N‐Dichloroimines and Their Reverse Conversion Mediated by Zinc in Methanol. Issue 48 (2nd December 2014) - Tang, Linlin; Zhang‐Negrerie, Daisy; Du, Yunfei; Zhao, Kang
Abstract A novel method for the synthesis of α, N‐dichloroimines through chlorination of enamines with PhICl2 as chlorine source is presented.